A simple slide test to assess erythrocyte aggregation in acute ST-elevated myocardial infarction and acute ischemic stroke: Its prognostic significance - Atla Bhagya Lakshmi; Prasad Uma; Ch Venkatachalam; G Siva Nageswar Rao (Wolters Kluwer Medknow Publications, 2011)
A simple slide test and image analysis were used to reveal the presence of an acute-phase response and to determine its intensity in subjects of acute myocardial infarction and acute ischemic stroke. Erythrocytes tend to aggregate during an inflammatory process. Evaluation of erythrocyte adhesiveness/aggregation is currently available to the clinicians indirectly by erythrocyte sedimentation rate (ESR), but ESR correlates poorly with erythrocyte aggregation, hence a simple slide technique using citrated blood was used to evaluate erythrocyte aggregation microscopically and also by using image analysis. Aims: (1) To study erythrocyte aggregation/adhesiveness by a simple slide test in subjects with acute ST-elevated myocardial infarction (STEMI), acute ischemic stroke and healthy controls. (2) To study the prognostic significance of ESR and erythrocyte aggregation/adhesiveness test (EAAT) in predicting the outcome after 1 week in subjects of acute myocardial infarction and acute ischemic stroke. Patients and Methods: Three groups of subjects were included in the study; 30 patients of acute STEMI, 30 patients of acute ischemic stroke, and 30 subjects with age- and gender-matched healthy controls. Citrated blood was subjected to simple slide test and ESR estimation by Westergren's method. Stained smears were examined under 400Χ and graded into four grades. Images were taken from nine fields; three each from head, body, and tail of the smear. The degree of erythrocyte aggregation was quantified using a variable called erythrocyte percentage (EP), by using the software MATLAB Version 7.5. A simple program was used to count the number of black and white pixels in the image by selecting a threshold level. Results: The mean ESR of the subjects with acute myocardial infarction (29 + 17.34) was significantly higher (P = 0.001) than the mean ESR of the control group (15.5 + 12.37). The mean EP of the subjects with acute myocardial infarction (69.91 + 13.25) was significantly lower (P < 0.001) than the mean EP of the control group (85.16 + 8.41). The mean ESR of the subjects with acute stroke (40.46 + 33.75) was significantly higher (P = 0.0005) than that of the controls (15.5 + 12.37). The mean EP of the stroke patients (70.59 + 11.30) was significantly lower (P < 0.001) than the mean EP of the controls (85.16 + 8.41). In subjects with acute myocardial infarction there was a significant negative correlation (r = −0.623) between ESR and EP. In acute stroke patients there was a significant negative correlation (r = −0.69) between ESR and EP. On performing standard error of proportions, P value was < 0.05. Conclusion: EAAT is a simple bedside test for erythrocyte aggregation, which indirectly reveals the presence and proportion of inflammation. This test has the potential to assess the prognosis of acute myocardial infarction and acute stroke. It can also be used as a screening test for high-risk individuals, so that necessary interventions could be adopted. However, further studies need to be conducted to establish standard protocols.